Kajian Linguistik Ayat-Ayat Ishraf dalam Al-Qur'an - Al Masithoh, Silvinatin; Al Ghifari, Fahmul Hikam (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2023)
The Qur'an is a miracle whose purity has been preserved to this day. One of the miracles of the Al-Qur'an lies in the beauty of its language, both in terms of its meaning and its words. Even this beauty could not be matched by the Quraysh people who were experts in the field of poetry and language. This research discusses the word form of the word